Optimization analysis of theoretical maximum specific gravity of asphalt mixtures in segregated areas of asphalt pavements based on asphalt medium method - Wang, Yikui; Xiong, Yuhong; Lian, Jianxiong; Wan, Kai; Chen, Bo; Cai, Xuran; Su, Shangwu; Huang, Qitao; Li, Weixiong; Xiong, Xuetang (Frontiers in Materials, 2025)
During the transportation, paving, and compaction of hot mix asphalt aggregate segregation occurs, leading to changes in the theoretical maximum specific gravity (Gmm) of the asphalt mixture. To accurately determine the Gmm of the asphalt mixture after segregation, field samples of the asphalt mixture were collected and analyzed using the ignition method to evaluate the extent of aggregate segregation at different locations (auger and paver overlap zones). The asphalt immersion method was employed to precisely measure the Gmm. Grey relational analysis was applied to identify influencing factors and their patterns of impact on Gmm, and the relational degree of each factor was determined. By introducing weight factors and variation ratios for each factor, an optimized prediction model for Gmm was established. The results indicate that the specific gravity ratio of coarse to fine aggregate is the most significant factor affecting Gmm. The error between the predicted air void content of the asphalt pavement based on the corrected Gmm and the core-measured values obtained via the asphalt immersion method does not exceed 0.5%. This model is suitable for estimating the Gmm of segregated asphalt mixtures, thereby improving the accuracy of compaction quality assessment in segregated areas of asphalt pavements.